2020
DOI: 10.3389/fbioe.2020.00850
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Expression and Biochemical Properties of A Thermo-Alkaline Pectate Lyase From Bacillus sp. RN1 in Pichia pastoris With Potential in Ramie Degumming

Abstract: Pectate lyases play an essential role in textiles, animal feed, and oil extraction industries. Pichia pastoris can be an ideal platform for pectate lyases production, and BspPel (a thermo-alkaline pectate lyase from Bacillus sp. RN1) was overexpressed by combined strategies, reaching 1859 U/mL in a 50 L fermentator. It displayed the highest activity at 80 • C, and maintained more than 60% of the activity between 30 and 70 • C for 1 h. It showed an optimal pH of 10.0, and exhibited remarkable stability over a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…However, it was observed that Cu 2+ ions could significantly enhance the mannanase activity of AfMan5A. A similar phenomenon was also observed in other studies regarding enzymes, such as amylase [28], pectate lyase [29] and laccase [30]. We speculate that this is likely caused by the structure changes of AfMan5A in the presence of Cu 2+ ions.…”
Section: Discussionsupporting
confidence: 88%
“…However, it was observed that Cu 2+ ions could significantly enhance the mannanase activity of AfMan5A. A similar phenomenon was also observed in other studies regarding enzymes, such as amylase [28], pectate lyase [29] and laccase [30]. We speculate that this is likely caused by the structure changes of AfMan5A in the presence of Cu 2+ ions.…”
Section: Discussionsupporting
confidence: 88%
“…pastoris GS115 strain containing the pPICHKAPel vector was used for the heterologous expression of pectate lyase (Pel from Bacillus sp. RN1) under control of the AOX1 promoter G/Pel ( Zheng et al, 2020 ). The P .…”
Section: Methodsmentioning
confidence: 99%
“…Pectate lyase activity was determined according to the method described by Zheng et al (2020) , with one modification: measuring the absorbance change at 235 nm with 2 mg PGA ml-1 as the substrate in 50 mM glycine–NaOH (pH 10.0) buffer containing 1 mM CaCl 2 for 40°C, 30 min. One unit (U) of pectin lyase activity was defined as the amount of enzyme that is required to produce unsaturated oligogalacturonide equivalent to 1 μmol of unsaturated diglucuronide min–1 using a molecular extinction coefficient of 4,600 M −1 cm −1 at 235 nm ( Zheng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, its industrial applications are limited. Under some of the required processing conditions, its stability and enzyme activity is decreased, and its efficiency in degumming ramie, cotton textiles, and pulp processing is not ideal (Xu et al 2021 ; Zheng et al 2020 ; Cheng et al 2019 ; Chiliveri and Linga 2014 ). Therefore, an alkaline pectin lyase with increased stability, heat resistance, and enzymatic activity is imperative to industrial processing.…”
Section: Introductionmentioning
confidence: 99%